Pendampingan Pembukuan Keuangan Sekolah Pada SD Negeri Emereuw, Organda, Distrik Abepura Kota Jayapura - Paulus Kombo Allo Layuk; Pascalina Van Sweet Sesa (The Community Engagement Journal, 2019)
In improving the quality of schools and education is closely related to school-based management (SBM), in terms of developing primary and secondary education. In the current conditions, SBM has not received good attention, and even tends to not be understood by the school as one of the important factors in supporting the expected implementation governance of educational sector. Schools have a duty to manage fincances based on financial management principles so that the money in circulation can be utilized optimally. Optimal school financial management forces schools to make the process of school financial management as good as possible. For this reason, efforts are needed in improving school financial management that can increase transparency and public accountability. In terms of school financial management, the role and competence of Human Resources (HR) are major factors in improving the quality of school financial management. Based on an analysis of school financial management problems that occured, it is necessary to provide assistance during the SBM management process.